Designed to binge? Exploring user perceptions of interface features on video streaming platforms - Cynthia A. Dekker; Anna Tverdina (Acta Psychologica)
Interface designs of video streaming platforms are reasoned to nudge users into binge-watching. More specifically, continued viewing is facilitated by algorithm-based personalized recommendations, autopreview (i.e., automatic playing of preview clips when browsing), and autoplay (i.e., automatic playing of new content after the previous content has ended). The present study aimed to shed light on the user perspective regarding these interface features by testing an extended Technology Acceptance Model. Data were collected from a cross-sectional online survey among 287 young adults. Results indicate that the extent to which a user has a preference for binge-watching as a viewing style predicts their usability perceptions of the platform's interface features. For autoplay specifically, it was revealed that perceived usefulness negatively correlates with perceived manipulation. This suggests that if an interface feature can fulfill people's usage goals (i.e., binge-watching), they feel less resistant to the impact the feature has on their usage. We discuss the importance of users' viewing style preferences and needs when designing and evaluating video streaming platform interfaces.